Epstein–Barr Virus and Hemophagocytic Lymphohistiocytosis - Marsh, Rebecca A. (Frontiers in Immunology, 2018)
Epstein-Barr virus (EBV) is a ubiquitous virus that infects nearly all people worldwide without serious sequela. However, for patients who have genetic diseases which predispose them to the development of hemophagocytic lymphohistiocytosis (HLH), EBV infection is a life-threatening problem. As a part of a themed collection of articles on EBV Infection and Human Primary Immune Deficiencies, we will review key concepts related to the understanding and treatment of HLH.